Earnings in eSports – The Case of StarCraft II Players - Ioana-Ruxandra LIE; Beatrice LEUȘTEAN; Andreea Maria Gabriela MILITARU (Communications of International Proceedings, 2020)
Even if their history can be tracked down to 40 years ago, from a scientific point of view, Esports can be considered as a new area of research. Until now, most of the literature on eSports focuses on the psychological and conceptual dimensions of this domain, and on legal concerns. The purpose of this article is to discuss the different sources of earnings in eSports and to analyze the earnings of a certain group of stakeholders, professional players of StarCraft II. We focus on the earnings and performance of the first 96 best players in the world and we find great variance in their earnings, according to performance. We conclude that if you are not top of the top, maybe should have a plan B as a career and source of income.
Keywords: Esports; Starcraft II; Professional Players’ Earnings; Descriptive Statistics; Correlation.